A series of dendronized hyperbranched polymers with dendritic chromophore moieties in the periphery: convenient synthesis and large nonlinear optical effects. Issue 24 (18th May 2016) - Yang, Haitao; Tang, Runli; Wu, Wenbo; Liu, Wei; Guo, Qing; Liu, Yingliang; Xu, Shengang; Cao, Shaokui; Li, Zhen
Abstract : Excellent optical transparency and NLO coefficients were achieved by introducing dendritic chromophore moieties to the periphery of dendronized hyperbranched polymers. Abstract : In this paper, by utilizing low generation nonlinear optical (NLO) dendrimers, in which one sulfonyl-based chromophore was used as an isolation chromophore for two nitro-based chromophores, as the initiator, a new series of dendronized hyperbranched polymers (DHPs), P1–P3, were prepared conveniently through one-pot atom transfer radical polymerization (ATRP) with satisfactory yields. Different from the previous NLO DHPs, of which dendritic NLO chromophores were usually linked into the interior architecture, the NLO chromophores were introduced into the periphery ofP1–P3 . Thanks to this special structure, all of them demonstrated large NLO effects. ForP1, its NLO coefficient d 33 value was tested to be 179.6 pm V −1, which, to the best of our knowledge, is among the highest values recorded so far for polymeric materials except for NLO dendrimers. In addition, the optical transparency ofP1–P3 could be further improved, due to the utilization of isolation chromophores. Coupled with its high NLO coefficient and convenient synthesis, P1 could serve as a good candidate for real optical application.